GOMAL-8, A HIGH YIELDING, DISEASE TOLERANT WHEAT VARIETY FOR IRRIGATED AREAS - M. H. Khan; N. Din; A. A. Khakwani; M. S. Baloch; M. Zubair; A.W. Khan (Journal of Animal and Plant Sciences, 2012)
Wheat variety Gomal-8, having parentage/pedigree “ATTILA” CM85836-4Y-0M-0Y-14M-0Y-5M-0Y-1SJ-0Y-0AP, was first tested at the Agricultural Research Institute (ARI), Dera Ismail Khan, during the year 1999-2000 in Regional Bread Wheat Yield Trial (RBWYT) received from Centro International de Mejoramiento de Maiz y Trigo (CIMMYT), Mexico. Out of 24 lines tested, high yielding and disease resistant line (DN-38) was selected which was then tested in various Preliminary Yield Trials (A-Test, B-Test, Micro Plot Trial) under irrigated condition at ARI, Dera Ismail Khan, during 2000-01. DN-38 was then included in Advanced Yield Trial (AYT) during 2001-02 and National Uniform Wheat Yield Trials (NUWYT) for two consecutive years from 2005-07. In NUWYT, DN-38 showed its dominance in high yield and resistance to yellow and leaf rusts. On the basis of its overall performance, DN-38 (Gomal-8) was approved by the Provincial Seed Council (PSC) as new wheat variety for general cultivation in irrigated areas of Khyber Pakhtunkhwa (KPK). The optimum sowing time for Gomal-8 is from 25th October to 25th November in KPK.
Keywords: Wheat; Triticum aestivum L.; variety; yield; disease resistance